Konseptualisasi dan Penentuan Kriteria-Kriteria Kenyamanan Kota - Ayu Candra Kurniati; Fahril Fanani (REKA RUANG, 2022)
The urban area is the most complex environment of the human habitat. Its development is strongly affected by the activity of its population. On the other sides, the livelihood of the urban population will be determined by the amenity provided within the urban area itself. It is expected that those urban amenities together with all of the social and economic activities occurring within an urban context may fulfill the basic needs of the urban population. This research was conducted to examine what aspect of urban amenities is strongly expected by the urban population. This research utilizes the content analysis method to investigate the criteria of urban amenities. Several pieces of literature have been collected and analyzed using an open coding approach to identify keywords regarding the urban amenity criteria. Research result shows that there are five most important aspects within the concept of urban amenity, which are supporting facility, cleanliness, urban temperature, noise, and security. Among those important aspects, public facility availability is considered the most critical aspect of urban amenities.